Evaluation of design pattern alternatives in Java. (31st December 2021) - Bijlsma, Lex A.; Kok, Arjan J. F.; Passier, Harrie J. M.; Pootjes, Harold J.; Stuurman, Sylvia
Abstract: Design patterns are standard solutions to common design problems. The famous Gang of Four book describes more than twenty design patterns for the object‐oriented paradigm. These patterns were developed more than twenty‐five years ago, using the programming language concepts available at that time. Patterns do not always fit underlying domain concepts. For example, even when a concrete strategy is a pure function, the classical strategy pattern represents this as a separate subclass and as such obscures the intent of this pattern with extra complexities due to the inheritance‐based implementation. Due to the ongoing development of oo ‐languages, a relevant question is whether the implementation of these patterns can be improved using new language features, such that they fit more closely with the intent. An additional question is then how we can decide which implementation is to be preferred. In this article, we investigate both questions, using the strategy pattern as an example. Our main contribution is that we show how to reason about different implementations, using both the description of a design pattern and design principles as guidance.